Residual stresses and metallurgic transformations induced by grinding. (14th April 2011) - Youssef, S.; Salem, W. Ben; Brosse, A.; Hamdi, H.
During grinding, commonly used as a finishing process, the integrity of part can be altered in many ways. Actually, the generation of high temperature level into the workpiece generally causes burning marks, structural and metallurgical transformation, and consequently influence the built up of residual stress. Therefore, a control of this process is of great importance to ensure both precise dimensions and small tolerance, required to have good working parts. The relationship between the metallurgic transformation and residual stress field generated by grinding of hardened AISI 52100 steel is discussed in this work. The obtained results indicate that the increasing of the grinding speed for low depth of cut induces a rise in the value of residual stress. This tendency is reversed for higher depths of cuts. Moreover, it is largely approved that there is a relationship between the states of the residual stress, metallurgical transformations and the kinetics of cooling induced by the grinding process.